Insight into the dissolution of lignite with ionic liquid [Bmim]cl. (15th February 2020) - Han, Song; Yu, Wenhao; Zhang, Hao; Lei, Zhiping; Shui, Hengfu; Ren, Shibiao; Wang, Zhicai; chong Yan, Jing; Li, Zhanku; Kong, Ying; Kang, Shigang; Pan, Chunxiu
Highlights: [Bmim]Cl pretreatment is accompanied by the generation and reaction of free radicals. [Bmim]Cl pretreatment increases the contents of carboxyl and ether bonds. [Bmim]Cl pretreatment reduces the content of hydrogen bond. [Bmim]Cl pretreatment breaks the cross-linked structure of lignite. Abstract: Ionic liquid as a green solvent have shown good performance in coal and biomass pretreatment, but the effects of ionic liquids pretreatment on the coal structures is still not properly understood. In this work, the changes of radical concentration in lignite during the pretreatment with ionic liquid 1-butyl-3-methyl-imidazolium chloride [Bmim]Cl were investigated by the electron spin-resonance spectroscopy (ESR) in detail and the effect of ionic liquid pretreatment on the change of coal structure was investigated by the diffuse reflectance infrared fourier transform spectroscopy (DRIFT) and thermogravimetric analysis (TGA). It was found that the pretreatment temperature and the ratio of [Bmim]Cl to lignite had a great impact on the radical concentration of lignite. The radical concentration of lignite decreased when the pretreatment temperature lower than 100 °C, which was attributed to the coupling of free radicals dissolved from coals. When the pretreatment temperature was higher than 100 °C, the radical concentration of lignite increased, which was attributed to the cleavage of weak bonds in lignite. It was also found that pretreatment with ionic liquid can fracture the oxygen-containing functional groups in the coal can be dissociated after pretreatment with ionic liquids, which leads to an increase in the content of carboxyl and ether bonds and a decrease in the content of hydrogen bonds.